P.026 Erenumab associated with high persistence among Canadian patients for preventive treatment of chronic and episodic migraine in real-world practice. (November 2021) - Bastien, N; Chhibber, S; Gladstone, J; Lanthier-Martel, J; Rochdi, D; Lan, T; Minhas, D; Neish, C
Abstract : Background: Real world use of oral prophylactic migraine therapies is often limited by poor patient tolerance. The objective of this study was to describe the demographics and clinical characteristics of patients prescribed erenumab following its launch in Canada (September 2018) and to evaluate the real-world treatment persistence and dose management. Methods: This was a retrospective, descriptive analysis of de-identified secondary patient data that includes baseline demographics, clinical characteristics, plus erenumab treatment management, collected through Novartis' Go Program® (Patient Support Program). Only data collected from patients with a documented informed consent were included in the analysis. Results: 14, 282 patients met eligibility criteria. The mean age of patients was 46.3 years, 83.0% were female, and 66.1% reported having ≥15 monthly migraine days. 52.5% were initiated on the 140 mg dose of erenumab and 59.3% of those who initiated the 70 mg dose escalated to 140 mg within 360 days. After 360 and 450 days, the KM-derived persistence was 71.0% and 63.4%, respectively. Conclusions: The high persistence reported here suggests that erenumab has a meaningful degree of tolerability in the real-world setting and increases confidence that the real-world use and benefits of erenumab will not be undermined by the poor persistence observed with traditional migraine prophylactic agents.